Clinical Presentation and Course of SARS-CoV-2 Infection in Health-Care Personnel Working in Dedicated COVID-19 Hospital During 2 Pandemic Waves in India. (20th December 2023) - Bindra, Ashish; Sharma, Neha; Joseph, Sheeba; Mathur, Purva; Malhotra, Rajesh; Khan, Maroof A.
Abstract: Introduction: Health-care personnel (HCPs) are predisposed to infection during direct or indirect patient care as well as due to the community spread of the disease. Methods: We observed the clinical presentation and course of severe acute respiratory syndrome coronavirus disease 2 (SARS-CoV-2) infection in HCPs working in a dedicated coronavirus disease 2019 (COVID-19) care hospital during the first and the second wave. Results: A total of 100 and 223 HCPs were enrolled for the first wave and the second wave, respectively. Cough, shortness of breath, sore throat, runny nose, and headache was seen in 40 (40%) and 152 (68%) ( P < 0.01), 15 (15%) and 64 (29%) ( P = 0.006), 40 (40%) and 119 (53.3%) ( P = 0.03), 9 (9%) and 66 (30%) ( P < 0.01), 20 (20%) and 125 (56%) ( P < 0.01), respectively. Persistent symptoms at the time of joining back to work were seen in 31 (31%) HCPs and 152 (68%) HCPs, respectively ( P ≤ 0.01). Reinfection was reported in 10 HCPs. Conclusions: Most of the HCPs had mild to moderate infections. Symptoms persist after joining back to work. Upgradation of home-based care and teleconsultation facilities for active disease and redressal of residual symptoms will be helpful.